SEED BIOPRIMING WITH PHANEROCHAETE CHRYSOSPORIUM ENHANCES TOLERANCE OF WHEAT TO SALT STRESS THROUGH IMPROVEMENT OF TAEXPB23 EXPRESSION - A. S.A. El-Sayed; H. E. S. Deif; E. S. A. Hashem; S. Fawzan (Journal of Animal and Plant Sciences, 2022)
Salt stress is one of the major abiotic stresses limiting the wheat productivity especially in arid and semi-arid regions. In our previous work, biopriming of wheat seeds with the fungus Phanerochaete chrysosporium strongly alleviate the salt stress response and improve the overall morphological and biochemical criteria of the plant. Thus, the objective of this study was to explore the mechanisms of salt tolerance of wheat in response to the fungal biopriming. The molecular expression of expansin proteins and the phytohormones levels of wheat under salt stress in response to fungal biopriming were estimated. The expression of expansin gene TaEXPB23, in wheat treated with 50 and 100 mM NaCl was increased by about 1.4 and 4fold, respectively, in response to biopriming with P. chrysosporium (EFB28) after 45 days of salt imposition. The levels of kinetin (KT), salicylic acid (SA), methyl jasmonate (MeJA), indole-3-acetic acid (IAA), and gibberellic acid (GA3) in wheat grown at 150 mM NaCl, was increased by about 4, 6, 8, 12, and 24-fold, respectively, in response to biopriming with P. chrysosporium, comparing to control plants (without fungal priming). As well as, the level of abscisic acid (ABA) in wheat grown at 150 mM NaCl was increased by about 10-fold with the fungal biopriming comparing to control plants (without fungal priming). Thus, from the metabolic and molecular analyses, the expression of expansin gene TaEXPB23 and concentration of phytohormones in wheat under high salt concentration, were strongly increased in response to fungal biopriming, that overall correlated with the tolerance of wheat to salt stress.
Keywords: Phanerochaete chrysosporium; Phytohormones; Expansins; Salt tolerance.